Morscher’s osteotomy in posttraumatic sequale of hip in adolescent using dynamic hip screw: case report - Garg, Gaurav; Dayma, Ratan; Meena, Rakesh (International Journal of Research in Orthopaedics, 2017)
Premature closure of proximal femoral epiphyseal plate can be a complication of hip dysplasia, Perthe’s disease, trauma or septic arthritis of hip. It may eventually result in Coxavara and shortening of femoral neck and upward migration of greater trochanter. Morscher’s osteotomy is an intertrochanteric osteotomy that can create valgusization with lengthening of femoral neck, correction of high riding greater trochanter and compensates for short limb length as a single stage procedure. The purpose of this case report is to evaluate early results of Morscher’s osteotomy fixed using paediatric dynamic hip screw in adolescence.